Penerapan Strategi Reading Aloud dan Index Card Match untuk Meningkatkan Hasil Belajar PAI Kelas II SD Istiqamah 2x11 Enam Lingkung - Yanuar Iqbal; Novita Juliana Sari Indah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to improve student engagement, collaboration, and learning outcomes in Islamic Religious Education (PAI) learning on the topic of recognizing the Asmaul Husana (the Names of Allah) using the reading aloud and index card matching strategies in second-grade students at SD Istiqamah 2x11 Enam Lingkung. This research is a CAR (Care of Action) conducted in two cycles. Each cycle consists of four stages: planning, action, observation, and reflection. For data collection, the researchers used techniques that included taking notes during the learning process and evaluating learning outcomes. The collected data were then analyzed, followed by conclusions, verification, and reflection on each cycle. Based on the research results, the researchers concluded that the implementation of the reading aloud and index card matching strategies can improve student engagement, collaboration, and learning outcomes in Islamic Religious Education (PAI) learning on the topic of recognizing the Asmaul Husana (the Names of Allah) in second-grade students at SD Istiqamah 2x11 Enam Lingkung. This study found that engagement, collaboration, and learning outcomes increased. In cycle I, student activity reached 70%, in cycle II it increased to 91.67%. Student cooperation in cycle I reached 75%, in cycle II it became 95.83%. Learning outcomes in cycle I reached 62.5%, in cycle II it increased to 95%. Based on this research, teachers in delivering material can apply learning strategies that are relevant to the material so that children do not feel bored and easily understand the material presented by the teacher.